A domain-specific marker for the hepatocyte plasma membrane. III. Isolation of bile canalicular membrane by immunoadsorption (The Rockefeller University Press, 1984)
Previous immunolabeling studies (Roman, L.M., and A.L. Hubbard, 1983, J. Cell Biol., 96:1548-1558; Roman, L.M., and A.L. Hubbard, 1984, J. Cell Biol., 98:1488-1496, companion paper) established leucine aminopeptidase (LAP) as a specific marker for the bile canalicular (BC) domain of the rat hepatocyte plasma membrane (PM). In this study, we have isolated membrane from a sonicated PM vesicle fraction using anti- LAP-coated Staphylococcus aureus cells as a solid-phase immunoadsorbent. The extent and specificity of the immunoadsorption were assessed by following the behavior of LAP (the BC marker) and 32P- labeled membrane phospholipids (a uniform membrane marker). The BC fraction obtained was significantly enriched in LAP (yield: greater than 70% of PM-LAP). Alkaline phosphatase, 5'-nucleotidase, and a 110,000-dalton glycoprotein, HA-4, were enriched in the BC fraction to the same extent as LAP (enzyme or antigen/LAP = 1.0). However, alkaline phosphodiesterase I was not enriched to the same degree (enzyme/LAP = 0.5). Contamination of this BC fraction by membrane derived from the sinusoidal domain and endoplasmic reticulum, as determined from the distribution of the asialoglycoprotein receptor and NADH cytochrome c reductase, respectively, was small (less than 13%).